Impact toughness of 12Cr1MoV steel. Part 2 – Influence of high intensity ion beam irradiation on energy and deformation parameters and mechanisms of fracture; Theoretical and Applied Fracture Mechanics; Vol. 83: ICEAF-IV Engineering Against Failure - Panin S. V. Sergey Viktorovich; Marushchak P. O. Pavel Orestovich; Vlasov I. V. Ilya Viktorovich; Sergeev V. P. Viktor Petrovich; Ovechkin B. B. Boris Borisovich; Neyfeld V. V. Vasily Viktorovich (2016, 2016)
Title screen